Feeding and oviposition preferences of Monochamus galloprovincialis on its main hosts Pinus sylvestris and Pinus pinaster - Koutroumpa, F.A.; Salle, A.; Lieutier, F.; Roux-Morabito, G. (ENTOMOLOGIA HELLENICA, 2009)
Considering the key role of Monochamus galloprovincialis (Olivier) (Coleoptera: Cerambycidae) in the dispersion of the pine wood nematode, Bursaphelenchus xylophilus (Steiner & Bührer) Nickle (Nematoda: Aphelenchoidea), in Europe, defining the host spectrum and preference of M. galloprovincialis is of primary importance for forest management. Therefore, comparative studies under laboratory conditions were performed in order to define the feeding and oviposition preferences of M. galloprovincialis adults as well as the larval development on Pinus sylvestris and Pinus pinaster. Both nutrition and oviposition were significantly higher on P. sylvestris. However, no difference was found when comparing larval survival on the two Pinus species even though larvae attended the fourth instar earlier when reared on P. sylvestris than on P. pinaster. The results of this study reinforce the suspicions of a future rapid propagation of the nematode, by M. galloprovincialis, into the Pine forests all over Europe.